2021
DOI: 10.3390/polym13213782
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Hydrogels: Preparation, Mechanism and Advancement in Biomedical Applications

Abstract: Polymeric hydrogels are widely explored materials for biomedical applications. However, they have inherent limitations like poor resistance to stimuli and low mechanical strength. This drawback of hydrogels gave rise to ‘‘smart self-healing hydrogels’’ which autonomously repair themselves when ruptured or traumatized. It is superior in terms of durability and stability due to its capacity to reform its shape, injectability, and stretchability thereby regaining back the original mechanical property. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 222 publications
0
44
0
Order By: Relevance
“…Hydrogels are hydrophilic polymeric materials that can hold a large volume of water in their three-dimensional networks . Lately, research has been carried out for various biomedical applications of hydrogels including tissue engineering as well as drug delivery. Importantly, the hydrogels used as drug delivery systems have shown diverse advantages in antimicrobial photodynamic therapy . Hydrogel-based drug delivery systems are highly advantageous for PDT in comparison to other conventional drug carriers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels are hydrophilic polymeric materials that can hold a large volume of water in their three-dimensional networks . Lately, research has been carried out for various biomedical applications of hydrogels including tissue engineering as well as drug delivery. Importantly, the hydrogels used as drug delivery systems have shown diverse advantages in antimicrobial photodynamic therapy . Hydrogel-based drug delivery systems are highly advantageous for PDT in comparison to other conventional drug carriers.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the antimicrobial photodynamic activity of the developed lignin-based nanocomposite as well as bare hydrogels, the live–dead cells staining assay was performed. , For this purpose, propidium iodide (PI) and 4′,6-diamidino-2-phenylindole (DAPI) dyes were used. The suspensions of both untreated and treated microbial cells were placed in the microcentrifuge tubes, followed by the addition of 10 μL of DAPI (0.05 mg/mL) and then propidium iodide (PI, 10 μL, 1 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…[ 27 ] A variety of dynamic covalent bonds have been introduced into the design of supramolecular hydrogels, including imine bonds, borate ester bonds, Diels–Alder reactions, arylhydrazone bonds, oxime bonds, and disulfide bonds. [ 28 ] The formation of dynamic borate esters in the IPBisoG hydrogel suggests its potential to be employed as an injectable hydrogel for local therapeutic purposes. To explore its injectability, essentially, the viscoelastic property of the IPBisoG hydrogel, rheological measurements were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts have been made to design synthetic hydrogels to provide the desired and unique combination of high mechanical properties with strong self-healing behavior by introducing special types of functional groups to provide various reversible chemical networks of hydrogels, such as hydrogen bonds, ionic bonds, hydrophobic interactions, host–guest interactions, π–π stacking, sometimes special covalent bonds, etc. [ 17 ] The most effective strategy for developing tough hydrogels has been observed in polyampholyte hydrogels by introducing a supramolecular system [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many review articles already reported various bonding mechanisms for self-healing performance [ 10 , 12 , 17 , 29 , 30 ]. However, the trade-off relation between self-healing and mechanical properties is yet to be reported and scrutinized.…”
Section: Introductionmentioning
confidence: 99%